Local Perianal Anesthetic Infiltration Is Safe and Effective for Anorectal Surgery - Poskus, Tomas; Jakubauskas, Matas; Čekas, Karolis; Jakubauskiene, Lina; Strupas, Kestutis; Samalavičius, Narimantas Evaldas (Frontiers in Surgery, 2021)
Background: General or regional anesthesia is predominantly used for anorectal surgery, however in the recent years more attention was drawn in the use of local anesthesia for anorectal surgery. In this study we present the technique and results of the use of local perianal anesthetic infiltration for minor anorectal operations. Methods: In this cohort study patients undergoing surgery for hemorrhoids, anal fissures and low anal fistulas were included. Posterior perineal block was induced with a mixture containing 0.125% bupivacaine and 0.5% lidocaine. All patients were followed up at 30 days either by a postoperative visit or a telephone call and all postoperative complications over the postoperative 30-day period were registered. Results: 1026 consecutive patients were included in our study. For all patients’ intraoperative analgesia was achieved after performing perianal anesthetic infiltration and no additional support from the anesthesia team was necessary in any of case. Complications were observed in 14 (1.4%). Urinary retention occurred in 5 (0.5%) cases. 6 cases of bleeding occurred after hemorrhoidectomy (0.6%) and 1 (0.1%) after lateral internal sphincterotomy. Perianal abscess developed for two patients (0.2%). Conclusions: Local anesthesia using posterior perineal block technique is safe and effective for intraoperative analgesia in anorectal surgery, saving a substantial operation cost by avoiding the involvement of an anesthesia team and resulting in minimal incidence of urinary retention and other complications.